2016
DOI: 10.1097/qai.0000000000000930
|View full text |Cite
|
Sign up to set email alerts
|

Reaching Suburban Men Who Have Sex With Men for STD and HIV Services Through Online Social Networking Outreach

Abstract: Grindr outreach by Public Health in a suburban county seems acceptable to MSM and leads to a 14-fold increase in MSM reached for counseling and education compared with a traditional outreach period. Further evaluation of technology-enabled approaches for STD/HIV prevention in suburban and rural MSM is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 13 publications
1
46
0
Order By: Relevance
“…Of 72 unique publications identified in our original search, 14 studies [1819, 20*, 21*, 22*, 23*, 24*, 25*, 26*, 27*, 28*, 29, 30**, 31**,32*] met the inclusion criteria and were published between April 2015 and March 2017 (Table 1). Inclusion criteria included articles in English that reported data on impact of online interventions in increasing access to HIV and sexually transmitted infections (STIs) related information, reaching and engaging online key populations in HIV/STIs awareness and/or demonstrating testing and prevention services uptake.…”
Section: Online-to-offline (O2o) Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 72 unique publications identified in our original search, 14 studies [1819, 20*, 21*, 22*, 23*, 24*, 25*, 26*, 27*, 28*, 29, 30**, 31**,32*] met the inclusion criteria and were published between April 2015 and March 2017 (Table 1). Inclusion criteria included articles in English that reported data on impact of online interventions in increasing access to HIV and sexually transmitted infections (STIs) related information, reaching and engaging online key populations in HIV/STIs awareness and/or demonstrating testing and prevention services uptake.…”
Section: Online-to-offline (O2o) Modelsmentioning
confidence: 99%
“…In a RCT of an intervention designed to increase HIV testing among MSM and TG by offering social support (spontaneous interactions delivered by health educators) within 4 geographically focused social media sites, Rhodes and colleagues report a significant increase in self-reported past 12-month HIV testing within intervention communities as compared to control arm (63.7% vs. 42.0%) [24*]. In a suburban California county, passive outreach on Grindr led to a 14-fold increase in MSM reached (in 5-years) for counseling, and 35% (197/562) of engaged users received testing/treatment referrals [25*]. Real-time telemedicine services adopting an unobtrusive approach, where online users contact providers and schedule appointment for a videoconferencing consultation session, are increasingly popular.…”
Section: Types Of O2o Models In Hiv Service Deliverymentioning
confidence: 99%
“…Several studies found app users to be more likely to report more sexual partners and condomless anal intercourse and to be at increased risk for sexually transmitted infections (STIs), including HIV [6, 811]. Sexual health promotion, such as to increase awareness of syphilis and syphilis testing [12], distribute HIV self-test kits [13], and increase linkage to HIV testing and treatment services at a local health department [14], have successfully occurred on these apps. Most of these efforts have occurred on one app in particular, specifically, Grindr, which was the first GPS-based social and sexual networking app of its kind.…”
Section: Introductionmentioning
confidence: 99%
“…The intervention was acceptable and increased the MSM reached for counselling and education by 14-fold. Although 816 MSM made contact with health educators through Grindr, only 14 people actually presented for testing 6. Another multiplatform intervention (A4A Radar, Grindr, Jack’d, Scruff) in North Carolina used a similar model in which health educators created profiles with photos of themselves dressed in business casual attire.…”
mentioning
confidence: 99%
“…Other strengths of this study include the large number of messages sent and the multiplatform nature of the intervention, enabling a broad reach. The study also had a larger proportion of referred people who followed up with testing compared with other similar interventions,6 though the overall number was still small.…”
mentioning
confidence: 99%